Antimicrobial susceptibility, beta-lactamase and enterotoxin production in Bacillus cereus isolates from clinical and food samples - Godic Torkar, K; Seme, K (Folia microbiologica, 2009)
The antimicrobial susceptibility of 30 clinical and 30 food Bacillus cereus isolates was determined. All isolates were susceptible to streptomycin, ciprofloxacin and gentamicin, 90 % of them to clindamycin and vancomycin, and 67 % to erythromycin. All isolates were resistant to amoxicillin with clavulanic acid, ampicillin, cefotaxime, ciprofloxacin, cloxacillin, cefotaxime with clavulanic acid and penicillin. The MIC values (determined by E-tests) were 48-256 mg/L for ampicillin, 0.19-1.5 mg/L for gentamicin, 0.125-1.0 mg/L for clindamycin, 0.047-4.0 mg/L for erythromycin and 1.5-16 mg/L for vancomycin. The MICs 4.6-18.75 g/L were observed for penicillin using the microdilution method. The presence of metallo-beta-lactamases was detected by E-test for 100 % of strains. Nonhemolytic diarrheal enterotoxin (NHE) was produced by 98.3 % of strains, while 31.7 % of them produced hemolytic diarrheal enterotoxin (HBL). Clinical isolates produced 10 % more HBL than food isolates. The psychrotrophic strains isolated from food samples produced NHE at 6.5 degrees C in 73 % of cases.
Keywords: mikrobiální testy citlivosti; teplota; beta-laktamasy; Food Contamination; enterotoxiny; lidé; Enterotoxins; Anti-Bacterial Agents; beta-Lactamases; grampozitivní bakteriální infekce; Temperature; Microbial Sensitivity Tests; kontaminace potravin; mnohočetná bakteriální léková rezistence; Drug Resistance, Multiple, Bacterial; antibakteriální látky; Bacillus cereus; Gram-Positive Bacterial Infections; Humans